The Construction of Identities in Space Inversion (the Case of Blagoveshensk and Chei-Che) - I. Y. Okunev; D. V. Basova; M. I. Tislenko (Vestnik MGIMO-Universiteta)
Abstract: The article represents a collective research of space identities at the Russian-Chinese border. The authors analyze the space configuration formed at the frontier of Blagoveshensk and Chei-Che regarding it as a social construction. It was an attempt to define the mechanisms of creating space identity at the flexible border marked by fluctuations of economic, political and cultural flows. There is a case of the Chinese town Chei-Che which is more open towards a Russian influence as well as to a deeper integration with the Russian side. Besides, there is a case of Blagoveshensk and its residents’ perception of their Chinese “neighbor”. Two major spatial bases of stateness are traditionally singled out: nation-building and threats to security or, in other words, labeling mental boundaries of community “Us” and actualizing “Others”. Threats to security or, rather, a discourse on them, form “Others” image, on the opposition to which is based nation and its geopolitical code. Existing stable centre-peripheral relations in each country put some thought about the third state-building mechanism - internal “Other”. Interregional differentiation within a state through establishing and maintaining the internal mental boundaries between centre and periphery comprises a mechanism to identify territories which need support to continue to act in compliance with national norms and thereof to facilitate stateness. Russian history could be interpreted as a periodic artificial reproduction of semi-periphery which sets the mental boundaries of internal “Other”. Suburban colonized territories which created an attractive image of Russian state in other territories’ eyes and were funded to the detriment of Russian internal regions became semi-periphery. The research conclusions derive from series field research made in two-cities, during which some sociological and qualitative methods were used. The authors make a conclusion that Blagoveshensk and Chei-Che have two different patterns of space identities determined by official discourse and ordinary perception.